Fragile peace in the face of catastrophe: Examining the immediate restraint and limitations of increasing militarisation in the Iran-Israel War of 2025 - Anees, M.S. (University of Colombo, 2025)
The short-lived conflict between Iran and Israel in 2025 is a clear illustration of the precarious equilibrium that controls the unstable Middle East. This paper examines how both sides’ acute awareness of the disastrous consequences of further escalation was a key factor in the swift containment of these intense hostilities. Despite long-standing animosity and existential concerns, the conflict was kept from degenerating into a full-scale regional war by the recognition of mutually assured destruction, which placed a strategic ceiling on it. Both Israel and Iran showed restraint by moderating their military actions and avoiding proxy involvement, reflecting an awareness of the severe consequences unchecked escalation would have on their political regimes, infrastructures, and societies. A crucial fact is highlighted by this mutual prudence: although military force is still used as a tool of policy, it is fundamentally limited when dealing with existential conflicts that have the potential to cause irreversible human and geopolitical disaster. The study also examines how US involvement in crisis management, regional power dynamics, and tactical choices were influenced by this recognition of catastrophic escalation. It contends that the containment of the war revealed the profound fragility of peace maintained primarily through deterrence and fear of mutual destruction rather than resolving underlying tensions. In conclusion, this study argues that any lasting peace in the area necessitates addressing the existential fears that fuel conflict and moving beyond military rhetoric. The 2025 war’s enduring fragility highlights the need for political solutions based on communication, fostering trust, and providing security assurances that lessen the need for force and prevent disastrous outcomes.
Keywords: Fragile balance; Geopolitical catastrophe; Proxy activation; Regional power dynamics; Transcending military posturing